Sleep apnoea is a risk factor for acute kidney injury after coronary artery bypass grafting. (17th November 2015) - Kua, Jieli; Zhao, Liang-Ping; Kofidis, Theodoros; Chan, Siew-Pang; Yeo, Tiong-Cheng; Tan, Huay-Cheem; Lee, Chi-Hang
Abstract : OBJECTIVES: Acute kidney injury (AKI) is a common complication in patients who undergo coronary artery bypass grafting (CABG). Sleep apnoea is associated with sympathetic activation, inflammatory reaction and plaque burden. The possible status of sleep apnoea as a risk factor for AKI after CABG has not been studied. METHODS: We recruited 169 patients for an overnight sleep study using a Food and Drug Administration-approved portable device before they underwent elective CABG. AKI after CABG was defined as a relative increase of greater than 25% or an absolute increase of greater than 0.5 mg/dl in the serum creatinine level from baseline within 5 days after CABG. A generalized structural equation model (gSEM) was then applied to ascertain whether sleep apnoea, defined as an Apnoea–Hypopnoea index (AHI) of 15 or higher, was associated with AKI after CABG after adjusting for the effects of confounding variables. RESULTS: Of the 150 patients (88.8%) who completed the study, the incidence of AKI after CABG was 22.7%. The mean AHI was higher in the AKI group (27.4 ± 19.8) than that in the non-AKI group (18.3 ± 16.5; P < 0.01). The prevalence of sleep apnoea was higher in the AKI group (64.7%) than that in the non-AKI group (45.7%; P = 0.05). The patients in the AKI group were older ( P < 0.01) and shorter ( P = 0.03) and had higher systolic blood pressures ( P = 0.01), greater waist circumferences ( P = 0.04) and larger left atrial diameters ( P < 0.01) than those in the non-AKI group. The patients in the AKI group had higher serum haemoglobin levels ( P = 0.04) and lower glucose levels ( P < 0.01) than those in the non-AKI group. A gSEM based on binomial distributions showed that sleep apnoea was an independent predictor of AKI after CABG (adjusted odds ratio, 2.89; confidence interval, 1.09–7.09; P = 0.03) after adjustment for the effects of haemoglobin, glucose levels, the left atrial diameter and systolic blood pressure. CONCLUSIONS: Sleep apnoea is prevalent and is associated with AKI after CABG. The data presented here provide the first insights into the potential of treating sleep apnoea to attenuate the risk of AKI after CABG.